Experimental and molecular docking investigation on DNA interaction of N‐substituted phthalimides: antibacterial, antioxidant and hemolytic activities. (6th July 2016) - Nayab, Pattan Sirajuddin; Irfan, Mohammad; Abid, Mohammad; Pulaganti, Madhusudana; Nagaraju, Chinthakunta; Chitta, Suresh Kumar; Rahisuddin,
Abstract: A series of Schiff base molecules derived from a phthalimide scaffold was investigated as efficient antibacterial, antioxidant and DNA‐interacting agents. The spectroscopic characterization of these derivatives was studied in detail using elemental analysis and spectroscopic techniques. The DNA‐binding profile of title molecules against Ct‐DNA (calf thymus) was investigated by absorbance, fluorescence, hydrodynamics and thermal denaturation investigations. The bacterial inhibition potential of these molecules was investigated against Escherichia coli and Staphylococcus aureus. Molecule 3c emerged as the most active against S. aureus (IC50 : 14.8 μg/mL), whereas compounds 3a and 3b displayed potential antibacterial activities against E. coli (IC50 : 49.7 and 67.6 μg/mL). Molecular docking studies of these compounds against GlcN‐6‐P synthase were carried out to rationalize antibacterial efficiency of these molecules. These newly synthesized molecules were screened for their scavenging capacity against 2, 2‐diphenyl‐1‐picryl‐hydrazyl (DPPH) and H2 O2 free radicals and the results were compared with ascorbic acid as synthetic antioxidant. The title molecules 3a, 3b and 3e showed less than 20% hemolysis, which indicated their significant non‐toxic behavior.